1996
DOI: 10.1002/stem.5530140705
|View full text |Cite
|
Sign up to set email alerts
|

The Regulated Expression of a TATA‐Less, Platelet‐Specific Gene, αIIb

Abstract: The megakaryocyte (MK)-specific integrin, alphaIIb, is the alpha-subunit of the alphaIIb/beta3 complex found on the surface of platelets. This complex is a receptor for fibrinogen and other ligands when platelets are activated. Because the alphaIIb gene is specifically expressed in MKs, this gene was studied as a potential model for MK-specific gene expression. Previous studies have defined some of the important regulatory elements in 912 bp of the immediate 5'-flanking region of this gene. These studies defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 46 publications
1
28
1
Order By: Relevance
“…Sp1-4 form a subgroup of the SP family that contain homologous activation domains and C-terminal zinc finger regions, which mediate DNA binding specificity (54). We limited our investigation to Sp1 and Sp3 because they are expressed in tissues where ␤8 is known to be expressed and have been shown to regulate expression of a wide array of integrin genes (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65). Their functions partially overlap as demonstrated by their knock-out phenotypes in mice (66 -68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sp1-4 form a subgroup of the SP family that contain homologous activation domains and C-terminal zinc finger regions, which mediate DNA binding specificity (54). We limited our investigation to Sp1 and Sp3 because they are expressed in tissues where ␤8 is known to be expressed and have been shown to regulate expression of a wide array of integrin genes (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65). Their functions partially overlap as demonstrated by their knock-out phenotypes in mice (66 -68).…”
Section: Discussionmentioning
confidence: 99%
“…Promoter studies of other integrins, such as ␣2, ␣3, ␣5, ␣6, ␣11, ␣IIb, ␤4, ␤5, CD11␤-␦, and CD18, have shown requirements for Sp1/Sp3 and/or AP-1 transcription factors and their cognate sites for expression (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(77)(78)(79). In particular, the promoter of ITGAV (integrin ␣v), the gene that encodes the heterodimerization partner of integrin ␤8, is also regulated by Sp1 and Sp3 (65).…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, as well as when a single Ets binding site is present, binding of cooperative transcription factor(s) is necessary for speci®c transactivation. c-Ets-1 and c-Ets-2 transactivate a large number of genes through interactions with a variety of factors (reviewed by Tymms and Kola, 1994), like Fos/Jun , Sp1 (Ge gonne et al, 1993;Block et al, 1996), GATA-1 (Lemarchandel et al, 1993). Essential Ets binding motifs cooperate with GATA elements for the tissue-speci®c expression of megakaryocytic genes such as glycoprotein (GP)IIb (Block et al, 1996;Lemarchandel et al, 1993;Martin et al, 1993), GPIba (Hashimoto and Ware, 1995), platelet factor four (PF4, Ravid et al, 1991), thrombopoietin receptor (MPL, Deveaux et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it is known that Rb, which interacts with Elf1, physically interacts with histone deacetylase HDAC1 (MagnaghiJaulin et al, 1998). Another example is Sp1, which interacts with many Ets factors (Block et al, 1996;Dittmer et al, 1997;Eichbaum et al, 1997;Krehan et al, 2000)), and has been shown to interact with HDAC1 (Doetzlhofer et al, 1999), repressing transcription. TEL is able to recruit co-repressors such as SMRT and mSin3A resulting in transcriptional repression Fenrick et al, 1999).…”
Section: Co-factormentioning
confidence: 99%